INDONESIA'S LABOUR LAW CHALLENGES IN THE BLUE ECONOMY SECTOR: PROTECTING FISHERMEN, MIGRANT WORKERS, AND MARITIME GIG WORKERS - Widiastiani, Nindry Sulistya (Jurnal Rechtsvinding: Media Pembinaan Hukum Nasional, 2025)
The blue economy holds significant potential for Indonesia's development, but labour law issues in this sector still face serious challenges. Fishermen and fisheries workers face uncertain employment status due to a profit-sharing system not clearly regulated by labour law. In contrast, maritime migrant workers remain vulnerable to exploitation and human trafficking despite existing migrant worker protection laws. Furthermore, the emergence of maritime gig workers in marine tourism services and digital platforms lacks the certainty of employment relationships or legal protection. This article aims to analyse the labour law challenges in the blue economy sector, identify regulatory issues faced by three categories of maritime workers, and propose ideas for more inclusive legal reform. The research method used is normative legal research, with both statutory and conceptual approaches. The study recommends regulatory reforms in cross-sectoral harmonisation, expanded social security, and developing a lex specialis on maritime workers, so that labour protection in the blue economy can be more equitable and sustainable.